EFFECT OF COMPENSATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE PRINGSEWU DISTRICT ELECTION COMMISSION - Yunita, Marini Mala; Alam, Iskandar Ali; Warganegara, Tri Lestira Putri (Journal of Management, Business and Social Sciences, 2024)
This study analyzes compensation and work discipline on employee performance in KPU Pringsewu Regency. This study was conducted with the aim of determining the effect of compensation on employee performance at the KPU Pringsewu Regency, knowing the effect of work discipline on employee performance at the KPU Pringsewu Regency, and to determine the effect of compensation and work discipline on employee performance at the KPU Pringsewu Regency. This study uses a type of quantitative research using analytical methods with data collection used by researchers are observation, documentation and questionnaires. The results obtained from this study know that there is an influence between compensation and work discipline on employee performance. Judging from the results of calculations that have been carried out, the significance value for the effect of compensation variables (X1) and work discipline variables (X2) simultaneously on employee performance variables (Y).